Isaiah's daughter [large type] : a novel of prophets & kings - Andrews, Mesu, 1963- (Center Point Large Print, 2019)
"In this epic Biblical narrative, ideal for fans of The Bible miniseries, a young woman taken into the prophet Isaiah's household rises to capture the heart of the future king"--